PENDEKATAN HOLISTIK HERBAL SEBAGAI INSPIRASI PADA PERANCANGAN INTERIOR PUSAT PENDIDIKAN DAN REKREASI HERBOLOGI: A HOLISTIC HERBAL APPROACH AS AN INSPIRATION IN THE INTERIOR DESIGN OF A HERBOLOGICAL EDUCATION AND RECREATION CENTER - Darwis Jayadi; Sri Rachmayanti; Yunida Sofiana (Fakultas Seni Rupa dan Desain, Universitas Trisakti, 2025)
Indonesia’s biodiversity and cultural heritage offer valuable inspiration for public interior design. This study proposes the design of a Herbology Education and Recreation Center aimed at providing both educational and recreational experiences for visitors. The concept adopts a holistic herbal approach, emphasizing the interconnectedness of interior elements with the principles of sustainability. A mixed-method research design was employed, consisting of questionnaires to capture public perceptions of herbal knowledge and a literature review to identify facility needs and examine holistic design theories. The findings indicate that the application of a holistic approach can generate interior concepts that align with the characteristics of Indonesian herbology. The proposed design not only functions as an educational facility but also integrates aesthetic, cultural, and economic values. Consequently, the project establishes a harmonious, interactive, and sustainable system that reinforces herbology as a local identity within the broader framework of education and public recreation.